Skin cancers of the face in an African Black population - Diallo M; Diadie S; Diatta B.A; Ndiaye M; Diop A; Dieng M.T (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
Introduction: The aim of this study was to evaluate the frequency and clinico-anatomical features of facial skin cancers in an African Black population.  Patients and methods: It was a retrospective, descriptive study of all cases of skin cancer localized on the face, seen in our department over a 21-year period.  Results: We collected 253 cases of cutaneous cancers, among which 48 cases (19%) were localized on the face. The mean age of the patients was 50 years, with a sex ratio (M/F) of 1.19. Squamous cell carcinoma (SCC) was the most common (54.2%), followed by primary cutaneous lymphomas (18.75%), Basal Cell Carcinoma (BCC) (14, 6%) and Darier-Ferrand dermatofi brosarcoma (4.2%). Melanoma, rhabdomyosarcoma, adnexal carcinoma and angiosarcoma were each observed in 1 case respectively (2%). Conclusion: In sub-Saharan Africa, the localization of skin cancer on the face is rare, dominated by SCC, which often occurs on precancerous skin lesions, especially actinic cheilitis and genodermatosis. The BCC and melanoma are exceptionally rare on the face.